Efficient and Stable All‐Inorganic CsPbIBr2 Perovskite Solar Cells Enabled by Dynamic Vacuum‐Assisted Low‐Temperature Engineering. Issue 4 (23rd December 2021) - Huang, Junyi; He, Shenghua; Zhang, Wenzhi; Saparbaev, Aziz; Wang, Yi; Gao, Yueyue; Shang, Luwen; Dong, Guohua; Nurumbetova, Lobar; Yue, Gentian; Tu, Yongguang
Abstract : Among all‐inorganic perovskite photoactive materials, CsPbIBr2 demonstrates the most balanced trade‐off between optical bandgap and phase stability. However, the poor quality and high‐temperature engineering of CsPbIBr2 film hinder the further optimization of derived perovskite solar cells (PSCs). Herein, a simple dynamic vacuum‐assisted low‐temperature engineering (merely 140 °C) is proposed to prepare high‐quality CsPbIBr2 film (VALT‐CsPbIBr2 film). Compared to HT‐CsPbIBr2 film processed via conventionally high temperature (280 °C), VALT‐CsPbIBr2 film presents higher crystallinity and more full coverage consisting of larger grains and fewer grain boundaries, which results in intensified light‐harvesting capability, reduced defects, and extended charge carrier lifetime. Benefiting from those improved merits, VALT‐CsPbIBr2 PSCs show lower trap‐state densities, more proficient charge dynamics, and larger built‐in potential than HT‐CsPbIBr2 PSCs. Consequently, VALT‐CsPbIBr2 PSCs deliver a higher efficiency of 11.01% accompanied by a large open‐circuit voltage of 1.289 V and a remarkable fill factor of 75.31%, being highly impressive among those reported CsPbIBr2 PSCs. By contrast, the efficiency of HT‐CsPbIBr2 PSCs is only 9.00%. Moreover, VALT‐CsPbIBr2 PSCs present stronger endurance against heat and moisture than HT‐CsPbIBr2 PSCs. Herein, a feasible avenue to fabricate efficient yet stable all‐inorganic PSCs via low‐temperature engineering is provided. Abstract : Herein, a simple dynamic vacuum‐assisted low‐temperature engineering is developed to prepare high quality CsPbIBr2 film (VALT‐CsPbIBr2 film). The derived VALT‐CsPbIBr2 PSCs yield a superior PCE of 11.01% with a remarkable fill factor of 75.31%, which both are impressive among the reported CsPbIBr2 PSCs. Meanwhile, VALT‐CsPbIBr2 PSCs feature stronger endurance against heat and moisture than control ones.